KAJIAN LITERATUR: PENGARUH MODAL KERJA DAN TOTAL HUTANG TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Effendi, Angelique -; Atmojo, Tirza Naftali; Chandra, Wenny -; Meiden, Carmel . (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
Working capital is a measurement of company liquidity which includes operational efficiency and the health of the company's financial performance in the short term. Therefore, this study aims to determine the magnitude of the development of working capital and total debt in calculating profitability. The technique used in this study was carried out using a systematic literature review method and using the Publish or Perish (PoP) software. In this study, the journals obtained were 200 journal articles and 30 journal articles were selected for analysis. Data in journal articles related to the effect of working capital and total debt on company profitability. This study uses a sample of companies listed on the Indonesia Stock Exchange from 2017 to 2022. The results of the study show that developments in working capital and total debt will have an impact on company profitability.